Citrus Nursery Production Guide, Chapter 4: Rootstock Selection - Ute Albrecht; Manjul Dutt; Jude Grosser (EDIS)
The large number of different rootstock varieties currently available for citrus production in Florida is unprecedented. This new 4-page article, chapter 4 of the forthcoming UF/IFAS Citrus Nursery Production Guide, provides information on rootstock uses in Florida, rootstock propagation, and the impact of tissue culture, as well as factors to consider when deciding which rootstock to plant. Written by Ute Albrecht, Manjul Dutt, and Jude Grosser and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1340